Perceptions of cycling among high school students and their parents. Issue 5 (28th May 2017) - Hopkins, Debbie; Mandic, Sandra
ABSTRACT: Cycling is a healthy, low-cost, and low-carbon alternative to motorized transport. As a relatively fast active mode of transport, cycling can overcome the distance barrier of walking, while also providing cardiovascular exercise and reducing demand for motor vehicle travel. The "cycling renaissance" has seen an increase in the number of cyclists in urban spaces, and there is evidence of increased investment in cycling infrastructure and cycle skills training in some places. Yet the number of high school students cycling to school is declining in many industrialized countries. Transport to school is a major contributor to daily traffic congestion, resulting in both local and global environmental concerns, and high school students have been relatively overlooked in research to date. In this paper, we present empirical material from a qualitative study of high school students and parents in Dunedin, Aotearoa New Zealand. Focus group sessions were conducted during 2014 and 2015 with students and parents separately, to explore their perceptions of modes of transport and transport to school decision making. Key findings relate to perceived safety, implicit messages, and social norms. We find that a complex range of factors contribute to perceptions of cycling safety, including features and perceptions of the built environment, traffic safety (including behaviors of other road users), previous cycling experiences (including accidents), and adolescents' cycling skills and on-road experiences. Overcoming concerns through behavioral and cultural interventions coupled with upskilling and thoughtful infrastructure may present a pathway to increasing rates of cycling.